Arteriovenous Access Outcomes and Risk of Major Cardiovascular Events in Patients with Reduced Ejection Fraction: A Retrospective Cohort Study - Nehal Naseer; Nadeem Ahmed Siddiqui; Fareed Ahmed Shaikh; Mohammad Zakriya (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the impact of ejection fraction on arteriovenous fistula maturation and patency, and to determine the incidence of major adverse cardiovascular events in end-stage renal disease patients undergoing arteriovenous fistula formation. Method: The retrospective cohort study was conducted at Aga Khan University Hospital, Karachi, and comprised data of patients who underwent arteriovenous fistula creation between January 2015 and December 2020. Using the American College of Cardiology guidelines, the patients were categorised into normal ejection fraction group A and abnormal ejection fraction group B, with the latter further divided into mild, moderate and severe dysfunction subgroups. Data on demographics, procedural details, arteriovenous fistula patency, and major adverse cardiovascular events within one year postoperatively were analysed. Data was analysed using Stata version 15. Results: Of the 127 patients, 92(72.4%) were in group A; 47(51.08%) females and 45(48.91) males with mean age 58.8 ± 13.3 years. The remaining 35(27.6%) patients were in group B; 24(68.6%) males and 11(31.43) females with mean age 57.9±14.7 years. Arteriovenous fistula patency rates were comparable between the groups; 75(81.5%) in group A and 31(88.6%) in group B. Major adverse cardiovascular events rates were significantly higher in group A 36(39.1%) compared to group B 16(12.6%) (p>0.05). Stroke occurred exclusively in group A 6(6.5%), while non-ST elevation myocardial infarction was the most common cardiac event; 15(16.3%) in group A and 7(20%) in group B. Conclusion: Preoperative ejection fraction did not significantly impact arteriovenous fistula patency in end-stage renal disease patients, but increasing ejection fraction dysfunction could trend towards lower patency. The higher major adverse cardiovascular events risk in normal ejection fraction patients suggested a complex interplay of factors requiring further investigation. Key Words: End-stage renal disease, AVF patency, Ejection fraction, MACE, Haemodialysis access.